Identification of actin mutants with neurodegenerative disease-like phenotypes via mutagenesis of the actin-ATP interface - Mann, Noah; Surabhi, Keerthana; Sharp, Josephine; Phipps, Mary; Becton, Maelee; Hill, Jahiem; Roberts, Davis; Szatmari, Erzsebet M.; Hughes, Robert M. (Frontiers in Cellular Neuroscience, 2025)
Cofilin-actin rods are a well-documented stress response in neuronal cells and their persistence is frequently associated with neurodegenerative disease. However, the role of specific actin residues in promoting the formation of cofilin-actin rods and other anomalous cytoskeletal structures is largely unknown. As it is increasingly suspected that specific mutations and post-translation modifications of actin may promote neurodegenerative disease, characterizing the role of these residues in cytoskeletal dysregulation is highly relevant. In this study, we focus on the actin-ATP interface, which has been proposed as a key mediator of cofilin-actin rod formation and the propensity of actin to respond to cellular stress. Using a light and stress-gated reporter of cofilin-actin cluster formation, we determine the impact of mutants associated with Actin-ATP binding on the propensity of actin to form anomalous structures in the presence and absence of applied cellular stress. This study identifies actin mutants that promote anomalous actin inclusions in HeLa cells and characterizes the manifestation of these phenotypes in cortical neurons. Mutations to the ATP phosphate tail-binding region of actin (K18A, D154A, G158L, K213A) were found to be particularly disruptive to actin phenotypes, and in several instances promote disease-associated actin-rich structures such as cofilin-actin rods and Hirano bodies. We find that these mutant phenotypes are largely consistent between cell types and display highly unusual inclusions in cultured cortical neurons, without leading to nuclear fragmentation and apoptotic death of the transfected cells. These mutants strengthen the association of residue-specific changes in actin with large-scale phenotypic and functional changes in the cytoskeleton, further implicating them in neurodegenerative disease progression.